A matemática nas compras em supermercado: utilização das quatro operações básicas no cotidiano de uma família - Burjack, Euneide Costa Coelho (Universidade Federal do Tocantins, 2023)
This article discusses the importance of the four basic math operations in the daily lives of families shopping in supermarkets. The proposal is to present a way of contextualizing content that is, apparently, pure abstraction. The mathematical knowledge involved in the addition, subtraction, multiplication and division operators that are routinely used in the purchase of items for daily or monthly use by consumers of first-need products from the basic food basket and hygiene items that have their prices displayed on the shelves of supermarkets, grocery stores and grocery stores in the city of Porto Nacional-TO. The investigation of how the use of operations are involved in purchases was carried out in a practical way, that is, customers with different consumption profiles were approached and authorization was requested so that they could be observed. We followed how they proceeded to check whether certain products offered were at attractive prices or not. At the end, some of the operations that customers performed during their purchases are presented.